The Prevalence of Hepatitis B Virus in Female Commercial Sex Workers - Bradley Jimmy Waleleng; J Kairupan; Nelly Tendean Wenas (The Indonesian Society for Digestive Endoscopy, 2006)
Background: The prevalence of hepatitis B infection in Indonesia was about 2-20%. To date, incidence rate of Hepatitis B Virus (HBV) in female Commercial Sex Workers (CSW) in Manado was not known. Objective: To investigate the prevalence and risk factors associated with HBV in female CSW. Methods: This is a descriptive-analytic study with cross-sectional design. Target population was female CSW in Manado. Results: Of 177 subjects, age range 15-49 years (27.87 ± 7.629), the most frequent age were 20-24 years with 56 subjects (31.6%). Serum HBsAg was positive in 8 (4.5%) subjects. Serum HBsAg was positive in 8 of 143 (5.6%) subjects with intercourse frequency 5 times weekly, 8 of 142 (5.6%) subjects with sexual partner 5 per week, 1 of 41 (2.4%) subject worked as CSW 1 year, 7 of 136 (5.1%) subjects worked as CSW for more than a year, and 1 of 110 (0.9%) subjects who used condom. Conclusion: Prevalence rate of hepatitis B in female CSW in Manado was 4.5%. There was significant relationship between condom usage and the prevalence of hepatitis B virus infection. There was relationship with some other risk factors but statistically insignificant. Keywords: hepatitis B virus, prevalence, commercial sex worker, condom usage